Cobalt oxide nanoparticle-synergized protein degradation and phototherapy for enhanced anticancer therapeutics. (February 2021) - Huang, Xueqin; Cai, Huaihong; Zhou, Haibo; Li, Ting; Jin, Hua; Evans, Colin.E.; Cai, Jiye; Pi, Jiang
Abstract: How to enable protein degradation pathways including the autophagy-lysosome pathway (ALP) and the ubiquitin-proteasome system (UPS) to enhance the efficacy of anticancer treatments remains a substantial challenge. Cobalt oxide nanoparticles (Co3 O4 NPs) have attracted interest in recent years for their potential use as a synergistic anticancer treatment, although their therapeutic mechanisms of action are still poorly understood. Here, we describe the synergistic use of Co3 O4 NPs as an autophagy inhibitor, chemosensitizer and photosensitizer, which manipulate protein degradation pathways (ALP and UPS) and photothermal therapy for enhanced anticancer treatments both in vitro and in vivo . We show that Co3 O4 NPs can induce autolysosome accumulation and lysosomal functions damage by inhibiting lysosomal proteolytic activity and reducing intracellular ATP levels. Notably, Co3 O4 NPs can be combined with the proteasome inhibitor, Carfilzomib (Cfz), to promote the accumulation of autophagic substrates, protein ubiquitination, and endoplasmic reticulum stress, and in doing so, inhibit cancer progression. By taking advantage of their photothermal conversion efficiency, Co3 O4 NPs can also serve as photothermal sensitizer, which synergistically enhances the anticancer efficacy of Cfz both in vitro and in vivo . In summary, we provide evidence of a nanomaterial-synergized, photothermal anticancer strategy that synergistically targets cancer cell survival pathways and may eventually serve to enhance the anticancer efficacy of established cancer therapeutics. Graphical abstract: Image, graphical abstract